Stem Cells in Cancer: From Mechanisms to Therapeutic Strategies - Laurence Haddadin; Xueqin Sun (Cells)
Stem cells have emerged as a pivotal area of research in the field of oncology, offering new insights into the mechanisms of cancer initiation, progression, and resistance to therapy. This review provides a comprehensive overview of the role of stem cells in cancer, focusing on cancer stem cells (CSCs), their characteristics, and their implications for cancer therapy. We discuss the origin and identification of CSCs, their role in tumorigenesis, metastasis, and drug resistance, and the potential therapeutic strategies targeting CSCs. Additionally, we explore the use of normal stem cells in cancer therapy, focusing on their role in tissue regeneration and their use as delivery vehicles for anticancer agents. Finally, we highlight the challenges and future directions in stem cell research in cancer.